Exploring the Effect of Attachment Styles and Winning or Losing a Status Contest on Testosterone Levels - Verbeke, Willem J.; Belschak, Frank; Ein-Dor, Tsachi; Bagozzi, Richard P.; Schippers, Michaéla (Frontiers in Psychology, 2018)
A person’s ability to form relationships and seek and attain social status affects their chances of survival. We study how anxious and avoidant-attachment styles and subsequent winning or losing affects the testosterone (T) levels of team members playing two status contests. The first is a management game played by teams striving to earn the most profits. Winners and losers emerge due to the cognitive endeavor of the players, which provokes intense status dynamics. Avoidant-attached winners do not show higher T levels whereas anxious-attached winners do. The second is an economic game which is rigged and favors some teams to become richer than others; teams have the option though to trade with each other and reduce the self-perpetuating rich-poor dynamics embedded in the game. Besides attachment styles, we here also explore how authentic pride as a self-conscious emotion affects team members’ T levels as players trade with others to create more fairness. As in the first status contest, players’ T levels are not significantly affected by their avoidant attachment style, neither as a main effect nor in interaction with winning or losing the game. However, similar to the first game, players’ anxious attachment style affects their T levels: anxious-attached players generate significantly higher T levels when winning the game, but only when experiencing high authentic pride during the game. In short, the moderating effects of attachment style on winners’ T levels are partly replicated in both status games which allows us to better understand the functioning of working models of attachment styles during and after status contests and gives us a better understanding of working models of attachment styles in general.